SCARCITY STRATEGY ANALYSIS ON SOCIAL MEDIA IN ENCOURAGING IMPULSE BUYING (A STUDY OF HIJRAH STORE CONSUMERS LHOKSEUMAWE) - Cut Sukmawati; Yulia Puspita; Teuku Zulkarnaen; Sutriani; Sufi (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to determine and analyze the effect of scarcity strategies on the social media platform Instagram on impulsive buying behavior of consumers at Hijrah Store Lhokseumawe. Using a quantitative approach with a survey method and simple linear regression, the study involved 100 active consumer respondents selected through purposive sampling. The collected primary data were then processed using SPSS version 25 software. Data analysis results indicate that the scarcity strategy (X) has a positive and significant effect on impulsive buying behavior (Y), evidenced by a calculated t-value of 2.469, which is greater than the critical t-value of 1.984 (sig. 0.015 < 0.05); therefore, the alternative hypothesis (Ha) is accepted. These findings align with the SOR theory, which asserts that the more effective the scarcity strategy implemented on Instagram as a stimulus, the stronger the consumers' psychological drive to make impulsive purchases as a response.